The development of organic-based systems for use in redox flow batteries - Shi, Raymond Rongsheng (Nanyang Technological University, 2021)
Organic compounds possess tremendous potential for energy storage as they are structural diverse and synthetically tuneable. Anthraquinone and o-tolidine displayed good chemical reversibility between their reduced and oxidised forms in the presence of trifluoroacetic acid. In a mixed reactant system (where both compounds existed together in solution), they were chemically compatible and stable under various conditions. The system also possessed two-electron per molecule transfer capability which is useful in designing a high energy battery system. With a controlled amount of diethyl malonate (DEM), the redox potential of vitamin K analogue (VKA) can be tuned to achieve a higher cell voltage. As such, the mixed reactant system comprising chemically modified VKA (VKA1) and a vitamin E analogue (VEA) exhibits an operational cell voltage of 1.23 V. The mixed reactants remain functional over a wide range of expected operational conditions, making it a reliable and stable organic-based electrolyte systems that is applicable towards the development of an all-organic battery for RFB applications.